The relationship of spirographic and hematological parameters in children with bronchial asthma - E. V. Tush; D. V. Azarnov; S. A. Pedchenko; M. V. Bogoroditskaya; T. E. Potemina; T. I. Eliseeva (Аллергология и Иммунология в Педиатрии)
.